2005
DOI: 10.1007/s11295-005-0019-8
|View full text |Cite
|
Sign up to set email alerts
|

Insertional mutagenesis in Populus: relevance and feasibility

Abstract: The recent sequencing of the first tree genome, that of the black cottonwood (Populus trichocarpa), opens a new chapter in tree functional genomics. While the completion of the genome is a milestone, mobilizing this significant resource for better understanding the growth and development of woody perennials will be an even greater undertaking in the years to come. In other model organisms, a critical tool for high-throughput analysis of gene function has been the generation of large mutagenized populations. So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
4
2

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 67 publications
(68 reference statements)
0
4
0
1
Order By: Relevance
“…To date, successful T-DNA-based activation tagging mutagenesis in trees has been reported only for poplar [14,15] and GA2-OXIDASE , a gibberellin catabolism gene, was the first tree gene that was isolated from a poplar T-DNA insertion population comprising 627 individuals [22]. In the following years, other T-DNA activation tagging poplar populations were produced and screened for developmental abnormalities including alterations in leaf and stem structure as well as overall stature by Harrison et al [21] The mutant frequency reported for the largest activation tagging poplar population (with 1,800 independent transgenic lines) was about 2.4%.…”
Section: Discussionmentioning
confidence: 99%
“…To date, successful T-DNA-based activation tagging mutagenesis in trees has been reported only for poplar [14,15] and GA2-OXIDASE , a gibberellin catabolism gene, was the first tree gene that was isolated from a poplar T-DNA insertion population comprising 627 individuals [22]. In the following years, other T-DNA activation tagging poplar populations were produced and screened for developmental abnormalities including alterations in leaf and stem structure as well as overall stature by Harrison et al [21] The mutant frequency reported for the largest activation tagging poplar population (with 1,800 independent transgenic lines) was about 2.4%.…”
Section: Discussionmentioning
confidence: 99%
“…Gene tagging through insertional mutagenesis approaches is a particularly appealing method in heterozygous trees that cannot be easily selfed, as it would generate dominant phenotypes. In Eucalyptus , the use of such an approach as a practical tool for genome‐wide gene characterization and breeding faces the same kinds of logistical and biological obstacles as found in Populus , but these might be overcome by large‐scale collaborative efforts (Busov et al ., 2005). To mitigate the biological and biochemical limitations to the study of wood formation in trees using mutant phenotypes, in vitro wood formation systems can be employed to introduce transgenes transiently or stably into growing wood‐producing tissue.…”
Section: Molecular Breedingmentioning
confidence: 99%
“…We have previously shown that activation tagging is a powerful forward genetics approach for gene discovery in Populus (Busov et al ., , , ; Yordanov et al ., , ; Trupiano et al ., ). Here, we report the identification and characterization of a poplar activation tagging mutant with increased lateral root (LR) development under high osmotic conditions that typically are prohibitive for LR development.…”
Section: Introductionmentioning
confidence: 99%